2015
DOI: 10.1007/s11230-015-9560-5
|View full text |Cite
|
Sign up to set email alerts
|

Description of Myxobolus balatonicus n. sp. (Myxozoa: Myxobolidae) from the common carp Cyprinus carpio L. in Lake Balaton

Abstract: 9 Abstract Myxobolus balatonicus n. sp. was detected 10 in the gill filaments of the common carp Cyprinus 11 carpio L. collected in Lake Balaton, Hungary. Its oval 12 plasmodia measuring 600-800 9 300-400 lm were 13 located intravasally in the filamental arteries. The 14 spores measured 11.2 ± 0.92 9 9.5 ± 0.41 9 7.4 ± 15 0.33 lm and had two equal polar capsules with six 16 filamental turns. Both morphology and DNA sequence 17 analysis revealed that M. balatonicus n. sp. is distinct 18 from the ten species of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The 18S rDNA sequence of Aurantiactinomyxon type 1 was make their way to Europe (Székely et al 2015a(Székely et al , 2015b …”
mentioning
confidence: 99%
“…The 18S rDNA sequence of Aurantiactinomyxon type 1 was make their way to Europe (Székely et al 2015a(Székely et al , 2015b …”
mentioning
confidence: 99%
“…The results of our present investigations contradict that statement. Although when describing the histology of some Myxobolus species (M. margitae Molnár, 2000, M. muelleri Bütschli, 1882, M. sommervillae, Molnár, Marton, Székely, Eszterbauer, 2010, M. arrabonensis Cech, Borzák, Molnár, Székely, 1915 on the basis of longitudinal sections, the present authors (Molnár, 2000;Molnár et al, 2006Molnár et al, , 2010Székely et al, 2015) tried to provide robust evidence for the intravascular development of plasmodia in the afferent branchial artery or the efferent branchial artery, an additional study using crosssectioned preparations was also recommended. As an exception, in their histological work Adriano et al (2009) clearly demonstrated plasmodia of M. salminus Adriano, Arana, Carriero, Naldoni, Ceccarelli, Maia, 2009 in the branchial vessels of Salminus brasiliensis (Cuvier) even in longitudinally sectioned preparations.…”
Section: Discussionmentioning
confidence: 76%
“…Cyprinus carpio Linnaeus; Lake Balaton, Hungary Székely et al (2015a) M. basuhaldari Székely, Cech, Chaudhary, Borzák, Singh et Molnár, 2015 P large, disporoblastic, roundish, 2-3 × 0.2-04, inside multilayered epithelium of gill filaments; SP ovoidal, bluntly pointed with a small knob at tapered anterior end, 7.3 (6.8-7.8) × 5.5 (5.1-6.2) × 3.7 (3.5-3.8); PC equal, pear shaped, 3.2 (2.9-3.7) × 2.1 (2.0-2.2), NC 5; additional host: Catla catla, same locality; GBAN: KM029974 for holotype, and KM 029975 and KM 029976 for paratypes. Fig.…”
Section: Discussionmentioning
confidence: 99%